2019
DOI: 10.1111/cid.12822
|View full text |Cite
|
Sign up to set email alerts
|

Antiseptic sealant and a nanocoated implant‐abutment interface improve the results of dental implantation

Abstract: Background Clinical measures and implant design innovation to improve primary osseointegration and reduce the bacterial contamination of the peri‐implant area are intended to reduce the incidence of late inflammatory complications in dental implantation. Purpose To study the effect of nanostructured coating and antiseptic sealant on the outcomes of dental implantation. Materials and methods Ninety‐six individuals were clinically supervised. In the first group (Screw Ti + sealant), a special antiseptic sealant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Factors that influence microleakage include IAI geometry, torque values, implant connection type, sterilizing methods, and use of adhesives and sealants 8,9) . Numerous in vivo and in vitro studies have examined microleakage of implants with different IAI geometry, confirming the high correlation between the type of implant-abutment connection and bacterial accumulation 6,[10][11][12][13][14][15][16][17][18][19] . While previous studies have focused on the leakage following definitive abutment placement, leakage during healing processes should also be investigated.…”
Section: Introductionmentioning
confidence: 78%
“…Factors that influence microleakage include IAI geometry, torque values, implant connection type, sterilizing methods, and use of adhesives and sealants 8,9) . Numerous in vivo and in vitro studies have examined microleakage of implants with different IAI geometry, confirming the high correlation between the type of implant-abutment connection and bacterial accumulation 6,[10][11][12][13][14][15][16][17][18][19] . While previous studies have focused on the leakage following definitive abutment placement, leakage during healing processes should also be investigated.…”
Section: Introductionmentioning
confidence: 78%
“…Numerous efforts were put in, to seal the microgap between the implant and the abutment for preventing microleakage at the implant-abutment interface. Several materials have been used to seal the implantabutment interface, such as, adhesive, silicone Oring, a silicon hermetic washer, chlorhexidine-thymol varnish, and 2% chlorhexidine solution, some commercial antiseptic sealents like Gapseal, Keiroseal are also available [28][29][30][31][32][33] .…”
Section: )mentioning
confidence: 99%
“…Zekiy concluded that an antiseptic sealant and a nanocoated implant-abutment interface will provide better osseointegration and stability to the implants with better outcomes 31) .…”
Section: )mentioning
confidence: 99%